Scoliosis screening results of primary school students (11-15 years old group) in the west side of Istanbul - KURU ÇOLAK, TUĞBA (SOC PHYSICAL THERAPY SCIENCE, 2015)
[Purpose] The present study aimed to find out the scoliosis prevalence 11-15 years old children and to create awareness about scoliosis. [Subjects and Methods] All of the children were assessed using the Adams Forward Bendings Test and a scoliometer. Sagittal plane changes such as kyphosis, lordosis, hypokyphosis, hypolordosis and anterior head tilt were screened. Children with trunk rotation angles (ATR) of 4 degrees or more were suspected of having scoliosis, and were evaluated for a second time for gibbosity height, arm-trunk distance, and ATR. [Results] A total of 2,207 children were screened and the evaluation revealed there were 11 girls (0.49%) with a Cobb angle of 10 degrees and more. The maximum Cobb angle was 43 degrees (right thoracic-left lumbar) and the maximum ATR was 12 degrees. Two children had kyphosis and lordosis, and one had hypokyphosis and was diagnosed as having idiopathic scoliosis. [Conclusion] Families should regularly check their children, even if they are not diagnosed as having scoliosis in school screenings. It is our opinion that our study increased the awareness of the families about scoliosis by screening, brochures and posters. In the future, if school screenings were performed as a routine procedure and scoliotic students were followed over the long term, the actual effectiveness of screening would be able to be detected.
Keywords: Scoliosis; School screening; Prevalence; IDIOPATHIC SCOLIOSIS; ADOLESCENTS; PREVALENCE; CHILDREN; WEIGHT; TURKEY; COST